Modern geoecological problems and their prevention (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Modern geoecological problems and the importance of their prevention is an important term for modern societies. These problems arise as a result of human activities and changes in nature and have a harmful effect on the ecological environment. These problems require more specific views, including economic, environmental, social and political. To deal with modern geoecological problems, it is necessary to carry out scientific research, collect and analyze data, and use new technologies.